2012
DOI: 10.1007/s10834-012-9295-2
|View full text |Cite
|
Sign up to set email alerts
|

Who Among the Elderly Owns Stocks? The Role of Cognitive Ability and Bequest Motive

Abstract: Conventional advice is to reduce risky investments as one ages. Such a generalized focus on risk avoidance may be inappropriate for elderly with longer life spans and those with financial goals that extend beyond their lifetime. To better understand risky asset holdings among the elderly, we investigated the effect of cognitive ability and bequest motive on stock ownership and stock purchase. Using the 2004 wave of the Health and Retirement Study, we found that one-third of elderly households held stocks and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 44 publications
1
17
0
1
Order By: Relevance
“…Previous cross‐sectional studies revealed relationships between cognitive function and extraordinary or non‐routine household behaviour, including stockholding . Kim and Hanna suggested that older people with cognitive impairment might not have the skills to manage investments . The present findings similarly suggest that extraordinary economic activities, as well as daily economic activities, among community‐dwelling elderly might be diminished with cognitive decline.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Previous cross‐sectional studies revealed relationships between cognitive function and extraordinary or non‐routine household behaviour, including stockholding . Kim and Hanna suggested that older people with cognitive impairment might not have the skills to manage investments . The present findings similarly suggest that extraordinary economic activities, as well as daily economic activities, among community‐dwelling elderly might be diminished with cognitive decline.…”
Section: Discussionsupporting
confidence: 66%
“…Older people with episodic memory and executive function impairment also score lower on financial literacy measures than those without them . Moreover, poor cognitive function, including memory function, is associated with lower shareholding, and those with cognitive decline have increased difficulty in managing investments . The Alzheimer's Society (UK) showed that 76% of people with dementia experience difficulty with banking, and 70% need assistance when paying bills .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that education is a proxy for prior income streams not captured by the current income measure, given the previously described challenges of modeling cumulative wealth with current income. Alternatively, education may directly affect wealth, perhaps due to the positive association between education and ownership of assets with higher risks and returns (Hanna et al 2010, Kim et al 2012). …”
Section: Part Iii: Evidence On Wealth Consequences and Determinantsmentioning
confidence: 99%
“…Cognitive ability has been found to be a fundamental factor of financial decision making (Bucher-Koenen and Ziegelmeyer 2011; Christelis et al 2010;Cole and Shastry 2009;Kim et al 2012). Frederick (2005) found that people with varying levels of cognitive ability made significantly different choices when faced with financial alternatives and noted a strong positive relationship between cognitive ability and decision quality.…”
Section: Literature Reviewmentioning
confidence: 99%